Thursday

April 24, 2014

April 24, 2014

Posted by **pinkpolkadots7** on Wednesday, October 11, 2006 at 6:52pm.

3x(a-5)=6

is x multiplication or variable

multiplication

Multiplication=*

Division=/

3x(a-5)=6

3*(a-5)=6

(3*a)+(3*5)=6

3a+15-15=6-15

3a=-9

3a/3=-9/3

a=-3

I hope this helps. I am not 100% sure this is right.

Or it can be expressed as:

3 x (a-5) = 6

(3 * a ) - (3 x 5) = 6

3a - 15 = 6

3a = 15 + 6 = 21.

a = 21 / 3 = 7

To verify the answer:

3 x (7-5) = 6

3 x 2 = 6.

3 x (a-5)=6

(a-5) = 6/3 = 2

a = 2 + 5 = 7

I dont understand that......can you explain?

3 x (7-5) =6

7-5) =6/3 =2

7 = 2+5 = 7

3x(a-5)=6 If multiplication as you state, then,

3*(a-5)=6

Multiply by 3 on the left side to clear the parentheses.

3a-15=6

Then move the -15 to the other side, changing the sign in the process.

3a = 6+15.

Combine terms on the right.

3a = 21

Divide both sides by 3

3a/3 = 21/3

a = 7. Now check the answer of 7 by putting it into the orginal equation.

3*(a-5)=6

3*(7-5)=6

3*(2)=6

6=6

The answer of a = 7 checks.

oops, I did not change the negitive to positive. Thats for correcting me.

i need help on order of operations

Do all operations inside the parentheses first.

Next, do any work with exponents or radicals.

Do all multiplication and addition from left to right.

Finally do all addition and subtraction from left to right

**Related Questions**

math - x+a=b/3x x= ? i understand that u bring the x to one side but the answer ...

Math - 2. Find the LCM and GCD of (2y^2 - 3a^2)x + (2a^2 - 3x^2)y and (2a^2 + ...

algebra - want to know if this right simplify and show all work -3x^2+4xy+7y^2+2...

Algebra 2 - Solve. 4a-2≤a+1≤3a+4 4a-2-1≤a+1-1≤3a+4-1 4a-...

Math - AlgebrAic factorization 1)6(2a-3)(a+7)+18(2a-3)(3a+2) 2) (3x-4)(5x+1)-(...

algebra - Given f(x) = 2x - 5, find f(-3a). F(x)= 2(-3a) -5 F(-3a) = 2(3a)-5 = 1...

algebra - solve using the multiplication principle -3a<-15 solve usins ...

Another Problem...PLz Help COunt Iblis - Statements Reasons 1. 3x - 7 = -4 2. 3x...

Math - Multiply and Simplify: (a^x-a^(-x))^3 =(a^x-a^(-x))(a^x-a^(-x))(a^x-a^(-x...

Math - Write each expression as the product of two binomials. 1) a^3 - 3a^2 + 3a...